Low Back Pain- How Significant are the Spinopelvic Parameters?. Issue 1 (April 2016) - Sai Krishna, M. L. V.; Sharma, Deep; Menon, Jagdish; Barathi, Deepak
Introduction: Since the discovery of pelvic incidence by Legaye et al. in 1998, many other sagittal spinopelvic radiographic parameters have been described as determinants of good sagittal balance. Alteration in these parameters has been linked to various spinal ailments producing degeneration to deformity. This have been proved by Roussouly et al. in his landmark paper, which showed a positive correlation between PI and Low Back Pain (LBP). However in the subsequent studies the same correlation could not be derived. Thus, we aim to study the role of high PI as a causative variable for Low back pain in our population. Materials and Methods : The study was approved by our institute review board and the ethical committee. We included all the patients visiting our OPD with complaints of LBP for more than three months and giving consent for the study. All patients underwent a thorough clinical and radiological examination, to rule out any apparent cause of LBP. We excluded patients with spinal deformity, fracture, infection, malignancy and with a history of previous spine surgery. A total of 67 patients were thus included in the study. Another age and sex matched group of asymptomatic volunteers ( n = 75) were also recruited as a control group. All the patients and volunteers underwent a standardized lateral sagittal digital radiograph of the whole spine including the base of the skull till the proximal ⅓ thigh (subject naturally standing up, looking horizontally, hands resting on a vertical support, upper limbs relaxed and elbows half bent). All the subjects were at a specific distance from the radiographic source and a single shot of x- rays have been used centering around D12. The sagittal spinopelvic parameters were measured using the Surgimap spine software version 2.1.2 by a single observer. The parameters measured were pelvic incidence PI, pelvic tilt PT, sacral slope SS, thoracic kyphosis TK, lumbar lordosis LL, lordotic and kyphotic vertebra. The comparisons were drawn between the patients and controls using appropriate statistical methods. Results: The mean values obtained in patients with low back pain were PI-48.04, PT-12.61, SS-35.5, LL-50.57 and TK-26.79. Corresponding values in healthy volunteers were PI-47.85, PT-13.03, SS-34.8, LL-54.68 and TK-24.03. We have found no statistically significant difference in the values of any sagittal spinopelvic parameters measured between the two groups. Conclusion: Based on the results derived from our study we conclude that there is no statistically significant correlation between any of the measured sagittal spinopelvic radiographic parameters and the occurrence of LBP.